Reproductive and Metabolic Responses of Early‐lactating Dairy Cows Fed Different Dietary Protein Sources. Issue 5 (2nd July 2015) - Tufarelli, V; Lacalandra, GM; Laudadio, V
Contents: Optimal reproduction is very closely tied with optimal nutrition, and early‐lactation diets in cows are critical to successful reproduction and monitoring is important. To evaluate the effects of different dietary protein sources on metabolic parameters and reproductive activity, a total of 36 Italian Friesian early‐lactating dairy cows were assigned for 16 weeks to three dietary treatments as follow: the control diet contained soya bean meal (SBM) as the main protein source, whereas the experimental diets contained faba bean (FB) or pea seeds (PS) as alternative protein sources. Diets were formulated to be isocaloric and isonitrogenous. Cow blood samples were collected, and plasma were analysed for metabolites, biological enzymes, β ‐hydroxybutyrate (BHBA) and non‐esterified fatty acids (NEFA). Feeding alternative protein sources had no effects on most metabolic blood profile, except for blood cholesterol, triglycerides and urea. Results from reproductive parameters indicated that cows fed FB diet had a lower insemination index, but a shorter calving to conception period and an improved conception rate and artificial insemination outcome, when compared to cows fed SBM or PS diets. It can be concluded that replacing conventional dietary SBM with alternative protein sources, especially FB, resulted in improved reproductive performances and metabolic parameters in early‐lactating dairy cows.